Towards Semantic-based RSS Merging - Getahun, F. (2009)
Merging information can be of key importance in several XML-based applications. For instance, merging the RSS news from different sources and providers can be beneficial for end-users (journalists, economists, etc.) in various scenarios. In this work, we address this issue and mainly explore the relatedness relationships between RSS entities/elements. To validate our approach, we also provide a set of experimental tests showing satisfactory results.